Media Coverage Report on Community-Based Breeding and SmaRT Pack Innovations - Getachew, Tesfaye; Rischkowsky, Barbara A.; Belay, Berhanu; Rekik, Mourad; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
In 2025, the media visibility of Ethiopia’s Community-Based Breeding Programs (CBBPs) and the Smart Pack innovation bundle expanded significantly across national, regional, and social media platforms, garnering recognition from both domestic and international networks. Supported by AICCRA and implemented by ICARDA in collaboration with the Ministry of Agriculture, research centers, and universities, CBBPs continued to demonstrate the power of climate-smart, inclusive, and data-driven livestock improvement.